Penilaian tahap kelestarian hidup menggunakan konsep POE (sebagai alat pengukuran) di apartment kediaman kerajaan Putrajaya - Mohamed Shafie, Anita (2010)
Research is done due to the rise of numbers of complaint on defects and damages in the government quarters. The motive of this research is to measure the satisfaction level of the tenants on their sustainable living, the quality of the apartment and the quality of maintenance, which influence the tenants’ health. Tenants view basically on the questions of sustainable design’s parameter, will be used for improvement to the quality living in the government homes. The main objective of the research is to identify the sustainable housing model for the government servants and the assessment of the sustainable design for the quarters, the tenants views are used for improvement. Data collection is done using questionnaire, where the relationship between demographic factors such as post, age, gender, living periods in the quarters, level of educations, government servants and the working years of respondent at P17RK1, P18R12, P9 Parcel 7 with the parameter questions is obtained. The results shows three sustainability living parameter questions achieved the first objective, and three of the sustainability design parameter questions achieved the second objective. The conclusions are drawn and the recommendations are made so that the sustainability living and sustainability design’s concept can be accepted by the tenants of the other areas. Among it is encourage developer to apply the GBI certifications, introduce facility manager’s role as an integrator to all the discipline involved with the facility, give awareness to the tenants on the sustainability living concepts and is required to ensure the maintenance plans are effectively done. Research on the As-Built Drawings and the related documents of building should be done for renovation. The research proves that the current government quarters for the selected areas achieved the sustainable house model for the government servants and the sustainability design assessment here for improvements are unnecessary.